To Study and Determine the Role of Anterior Segment Optical Coherence Tomography and Ultrasound Biomicroscopy in Corneal and Conjunctival Tumors - Katleen Janssens; Michelle Mertens; Noémie Lauwers; Rob J. W. de Keizer; Danny G. P. Mathysen; Veva De Groot (Journal of Ophthalmology)
Purpose. To analyze and describe corneal and conjunctival tumor thickness and internal characteristics and extension in depth and size and shape measured by two noninvasive techniques, anterior segment optical coherence tomography (AS-OCT) and ultrasound biomicroscopy (UBM). Design. Systematic review. Methods. This systematic review is based on a comprehensive search of 4 databases (Medline, Embase, Web of Science, and Cochrane Library). Articles published between January 1, 1999, and December 31, 2015, were included. We searched for articles using the following search terms in various combinations: “optical coherence tomography”, “ultrasound biomicroscopy”, “corneal neoplasm”, “conjunctival neoplasm”, “eye”, “tumor” and “anterior segment tumors”. Inclusion criteria were as follows: UBM and/or AS-OCT was used; the study included corneal or conjunctival tumors; and the article was published in English, French, Dutch, or German. Results. There were 14 sources selected. Discussion. Several studies on the quality of AS-OCT and UBM show that these imaging techniques provide useful information about the internal features, extension, size, and shape of tumors. Yet there is no enough evidence on the advantages and disadvantages of UBM and AS-OCT in certain tumor types. Conclusion. More comparative studies are needed to investigate which imaging technique is most suitable for a certain tumor type.